(untitled) - Shakespeare, William (Hoboken, N.J., 2007)
An authoritative, accessible overview of history's greatest literary figure. The great dramatist Ben Jonson wrote that William Shakespeare "was not of an age, but for all time." In the nearly four centuries since his death, Shakespeare's plays still have a tremendous impact on everything from the classroom to popular culture. Now you can have at your fingertips all the vital details on the most influential writer in the history of the English language--straight from one of the most trusted sources of information in the world. In Shakespeare, Encyclopaedia Britannica presents a concise and balanced overview of the Bard's life, work, and legacy. From his upbringing in Stratford to his early theater career in London, from his poetry and plays to the controversy surrounding his authorship, from his contemporaries and collaborators to his critics past and present, this comprehensive guide provides the necessary background to appreciate Shakespeare's unique place in world literature.
Keywords: Dramatists, English,Kịch, tiếng Anh,Shakespeare; Early modern, 1500-1700,Đầu hiện đại, 1500-1700